An investigation into post-graduate physiotherapy education in South Africa - S. H. Irwin-Carruthers (AOSIS, 1991)
This article outlines the development of post-graduate physiotherapy education in South Africa and the problems encountered. The method and results of two surveys are discussed. The first, conducted in 1986, ascertained involvement and interest in post-graduate study, and the reasons for non-participation. The respondents' needs and preferences were also analysed. The second (1989) survey investigated the extent to which universities were meeting these needs. The difference between clinical specialisation and academic post-graduate study is discussed and the progress made in the former is detailed. Proposals are made for overcoming current problems in postgraduate programmes, including delineating objectives and competencies, optimum management of existing resources and developing new resources. The question remains as to whether the direction in which post-graduate programmes are developing at present can be justified in terms of the needs of the population.